The 4-hour standard is a meaningful quality indicator: correlation of performance with emergency department crowding. (February 2017) - Higginson, Ian; Kehoe, Anthony; Whyatt, Justin; Smith, Jason E.
Abstract : Background: The 4-h standard performance is a controversial quality indicator. Crowding in emergency departments (EDs) causes increased patient morbidity and mortality. The aim of this study was to investigate the relationship between 4-h standard performance and ED crowding as measured by occupancy. Methods: A retrospective observational study was carried out using the computerized Emergency Department Information System. Daily occupancy was considered in three ways: as minutes per day spent at occupancy thresholds of 70, 80, 90 and 100%; as the peak occupancy of resuscitation and majors beds at any point in the day; and as a percentage of the total potential ED bed minutes used during the day. Results: An inverse relationship was observed between occupancy and 4-h standard performance using each method. Performance could be sustained at 70% occupancy, but deteriorated in a linear manner at a progressively increasing rate at 80, 90 and 100% occupancy (all P <0.01). A stepwise decrease in the mean performance was observed with increasing peak occupancy ( P <0.001). A similar decrease in performance was observed with increasing 24-h overall occupancy ( P <0.001). Conclusion: This study has identified a clear and consistent correlation between ED crowding and performance against the 4-h standard. Because crowding is associated with harm, the 4-h standard is a meaningful quality metric for UK hospitals. Systematic measurement of ED crowding using occupancy may play a role in improving the quality of care delivered within the urgent care system.